2023
DOI: 10.1126/sciadv.adh9543
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 retrotransposons drive human neuronal transcriptome complexity and functional diversification

Raquel Garza,
Diahann A. M. Atacho,
Anita Adami
et al.

Abstract: The genetic mechanisms underlying the expansion in size and complexity of the human brain remain poorly understood. Long interspersed nuclear element–1 (L1) retrotransposons are a source of divergent genetic information in hominoid genomes, but their importance in physiological functions and their contribution to human brain evolution are largely unknown. Using multiomics profiling, we here demonstrate that L1 promoters are dynamically active in the developing and the adult human brain. L1s generate hundreds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In fact, lineage specific enhancers that are enriched in insertions of a specific family of SINEs play important roles in mammalian neural development 73,74 . Recently, an elegant study determined that L1s are expressed in apical and basal progenitor cells and early born neurons present in developing human fetal forebrain; silencing of a specific L1 insertion in cerebral organoids developed from these cells resulted in smaller size 75 . Therefore, it is possible that RTEs also regulate gene expression programs that control early brain development in Drosophila , and future experiments involving scRNA-seq of wild type, condensin mutant and ago2 mutants may shed light on these questions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, lineage specific enhancers that are enriched in insertions of a specific family of SINEs play important roles in mammalian neural development 73,74 . Recently, an elegant study determined that L1s are expressed in apical and basal progenitor cells and early born neurons present in developing human fetal forebrain; silencing of a specific L1 insertion in cerebral organoids developed from these cells resulted in smaller size 75 . Therefore, it is possible that RTEs also regulate gene expression programs that control early brain development in Drosophila , and future experiments involving scRNA-seq of wild type, condensin mutant and ago2 mutants may shed light on these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Although most transposable elements have been rendered inactive through mutation, long interspersed element-1 (LINE-1 or L1) retrotransposition continues to diversify human genomes [64]. LINE1 expression cause a large number of DSBs at long neural genes due to replication stress activating the DNA damage response whereby L1 retroelement mobilization in the brain is considered to diversify neuronal cell populations [65], further lending credence to McClintock's proposal of a 'dynamic genome' on this level as well [66].…”
Section: American Scientist Barbara Mcclintock Was Awarded the Nobel ...mentioning
confidence: 97%
“…Although most transposable elements have been rendered inactive through mutation, long interspersed element-1 (LINE-1 or L1) retrotransposition continues to diversify human genomes [64]. LINE-1 expression causes a large number of DSBs at long neural genes due to replication stress activating the DNA damage response whereby L1 retroelement mobilization in the brain is considered to diversify neuronal cell populations [65], further lending credence to McClintock's proposal of a 'dynamic genome' on this level as well.…”
Section: Chromosomal Fragility As An Environmental Stress Related Evo...mentioning
confidence: 99%
“…Environmental influences such as stress, infections, nutrition, or other environmental factors that affect the mother, appear to influence L1 mobility in newborn neurons during embryonic development. Induction of L1-induced neuronal diversity could increase the neurobehavioral spectrum originating from a single genome [65]. Several gene ontologies were identified that were affected by the L1 burden.…”
Section: Does Novelty Stress Drive the Evolution Of Form Function And...mentioning
confidence: 99%